ANALYSIS OF THE PUBLIC POLICY OF BASIC SANITATION IN THE MICRO-REGION OF PIRES DO RIO - GO AS AN INSTRUMENT FOR THE REALIZATION OF THE RIGHT TO HEALTH (CIPEEX, 2022)
THE URBANIZATION PROCESS BROUGHT WITH IT, BESIDES DEMOGRAPHIC GROWTH AND PROSPECTS FOR BETTER LIVING CONDITIONS, THE NEED TO THINK ABOUT HOW TO PROVIDE HEALTHY, INCLUSIVE AND DEMOCRATIC SPACES FOR ALL CITY INHABITANTS. HOWEVER, THERE IS MUCH TO BE ADVANCED, ESPECIALLY REGARDING THE LACK OF BASIC SANITATION, A REALITY IN MANY BRAZILIAN MUNICIPALITIES.
Keywords: right to the city; sanitary right; Urbanization